2013
DOI: 10.1080/15017419.2012.761159
|View full text |Cite
|
Sign up to set email alerts
|

Self-presentations and intellectual disability

Abstract: The aim of this article is to demonstrate how some young individuals who are labelled as having intellectual disabilities present themselves and how they understand and relate to the fact that they are included in the category of intellectual disability. The article draws on findings from a study based on participant observation and semi-structured interviews with seven young adults about their self-understanding and daily life experiences. During the data gathering period, which lasted for two years, the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…Further to this, despite most people being aware of their intellectual disability (irrespective of the actual level of awareness and understanding), the results from many of the studies suggest that it may not be considered an important part of their identity. Instead, they often focus on other attributes, roles, and competencies when describing themselves, and rarely refer to their intellectual disability in self‐presentations (Davidson, Smith, & Burns, ; Dorozenko, Roberts, & Bishop, ; Kittelsaa, ). Finlay and Lyons () found that when individuals with intellectual disabilities were asked to describe themselves (but were not asked specifically about their intellectual disability) in an interview, only four out of 36 participants used the label (or a synonym) when referring to themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Further to this, despite most people being aware of their intellectual disability (irrespective of the actual level of awareness and understanding), the results from many of the studies suggest that it may not be considered an important part of their identity. Instead, they often focus on other attributes, roles, and competencies when describing themselves, and rarely refer to their intellectual disability in self‐presentations (Davidson, Smith, & Burns, ; Dorozenko, Roberts, & Bishop, ; Kittelsaa, ). Finlay and Lyons () found that when individuals with intellectual disabilities were asked to describe themselves (but were not asked specifically about their intellectual disability) in an interview, only four out of 36 participants used the label (or a synonym) when referring to themselves.…”
Section: Resultsmentioning
confidence: 99%
“…They wanted to be treated like ordinary citizens and did not wish to be identified as people with disabilities (Olin & Ringsby Jansson 2009;Molin 2008;Kittelsaa 2014). Like most people, they did not wish to be placed in categories which had a negative connotation (Kittelsaa 2014). The result shows that the participants wished to express their opinions and to influence their working day.…”
Section: Discussionmentioning
confidence: 99%
“…Young people with intellectual disabilities want to be independent and live like others do. They do not want others to define who they are (Kittelsaa 2014). Expectations from teachers are important for young adults in the transition from school to work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, important to note that this does not exclude the possibility of other people with intellectual disability being unware of this label or wanting to deny those aspects that make them 'different' in the eyes of broader society. Indeed, the label 'intellectually disabled' is so negatively loaded that distancing oneself from this categorical identity can serve a protective function(Kittelsaa 2013). burdensome Some Members interviewed spoke of being a burden or an inconvenience to their parents, suggesting that they had internalised a stigmatised view of self.…”
mentioning
confidence: 99%